Diplomatic Correspondences of the Sheybanid and Ashtakhanid Sovereigns with Iran and India - Dr. Azamat Ziyo (Researchparks Publishing, 2023)
Diplomatic correspondences disclose the history of relations between states. They show political and economic ambitions of sovereigns towards a particular country or countries. The correspondences also explore the positions of certain states in relation to other events happening around them or using benefiting of other powers in order to weaken the third actor. The correspondences between Shaybanid and Ashatarkhanid rulers with Indian Baburid monarchs and Iranian shahs illustrate the calls to take joint steps in order to weaken or withstand the other power, territorial disputes and supremacy of unilateral interests.